Pengembangan Lembar Kerja Siswa Pengamatan Berorientasi Strategi Comparison And Contrast Web Materi Spermatophyta - ZULFA, AYULUBNA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2012)
Abstract— Development of observational student worksheet using comparison and contrast web strategy in Spermatophyte’s material was aimed to know the student worksheet’s feasibility, student’s activity by implementation of worksheet and students’ response towards the worksheet’s readability. This developing consists of several stages, i.e. planning, reviewing, conducting and evaluating. The results of this research are: the review result showed that the developed observational student worksheet using comparison and contrast web strategy is appropriate to be used in the field. Students showed positive response towards student’s activities by implementation of student worksheet and towards the use of student worksheet as a learning activity. Keywords: student worksheet, spermatophyte, observation, comparison and contrast web.